2009
DOI: 10.1002/jmri.21756
|View full text |Cite
|
Sign up to set email alerts
|

Optimized high‐resolution mapping of magnetization transfer (MT) at 3 Tesla for direct visualization of substructures of the human thalamus in clinically feasible measurement time

Abstract: Purpose:To optimize contrast-to-noise and spatial resolution of a FLASH-based magnetization transfer (MT) protocol for visualization of substructures in human thalamus. Materials and Methods:Healthy adults were examined at 3 Tesla with a three-dimensional (3D) spoiled gradient-echo sequence. The signal-to-noise ratio (SNR) was increased by averaging eight bipolar echo acquisitions (mean echo time ϭ 12.3 ms; bandwidth ϭ 370 Hz/pixel). Three isotropic datasets with different weighting (proton density: flip angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
32
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 20 publications
5
32
3
2
Order By: Relevance
“…Besides the most frequently used heavily T2-weighted fast spin-echo [20,31,38] new sequences including quantitative T1 and T2 imaging [39,40] , T2* mapping [41][42][43] and susceptibility-weighted imaging (SWI) [44] , have been proposed to improve the visibility of the target structures. For the ZI no respective data exists.…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 99%
“…Besides the most frequently used heavily T2-weighted fast spin-echo [20,31,38] new sequences including quantitative T1 and T2 imaging [39,40] , T2* mapping [41][42][43] and susceptibility-weighted imaging (SWI) [44] , have been proposed to improve the visibility of the target structures. For the ZI no respective data exists.…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 99%
“…Whether SWI images at 3T provide a similar contrast and if the combination of the different contrasts of T1 and SWI further improves segmentation need further investigation. Gringel et al 21 reported that with multiparameter magnetization-transfer maps, improved contrasts can be obtained within the thalamus in a measurement time of 23-25 minutes, but postprocessing is required to calculate the multiparameter maps. The multiecho fast low-angle shot sequence needed is not available as a standard sequence on most scanners; this requirement is currently another drawback for clinical application.…”
Section: Figmentioning
confidence: 99%
“…[4][5][6][7][8] In parallel to the effort of providing stereotactic atlases that incorporate clinical imaging-based anatomic correspondences, 9 it is desirable to optimize MR imaging sequences and image-processing techniques for the direct identification of thalamic nuclei. [10][11][12] A promising technique to noninvasively chart the human thalamus is diffusion tensor imaging 13 and subsequent probabilistic tractography, which can be applied to map the networks of thalamocortical connectivity. [14][15][16] Such methods are based on the fact that various thalamic nuclei present differential interconnections; therefore, this information can be used to subdivide the thalamus into domains that have different dominant connections with preselected cortical domains.…”
mentioning
confidence: 99%